2020
DOI: 10.1016/j.chembiol.2020.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Antiviral Efficacy of RNA-Dependent RNA Polymerase Inhibition by Combination with Modulators of Pyrimidine Metabolism

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 52 publications
5
17
0
Order By: Relevance
“…Recent studies have revealed that pyrimidine metabolism participates in SARS‐CoV‐2 infection 32,33 . In the present study, KEGG analysis results demonstrated that pyrimidine metabolism and steroid hormone biosynthesis are the major pathways involved in the host cells after SARS‐CoV‐2 infection.…”
Section: Discussionsupporting
confidence: 52%
“…Recent studies have revealed that pyrimidine metabolism participates in SARS‐CoV‐2 infection 32,33 . In the present study, KEGG analysis results demonstrated that pyrimidine metabolism and steroid hormone biosynthesis are the major pathways involved in the host cells after SARS‐CoV‐2 infection.…”
Section: Discussionsupporting
confidence: 52%
“…Liu et al . [ 34 ] showed that suppression of de novo pyrimidine synthesis in antiviral treatment strategies, apart from RNA-dependent RNA polymerase inhibition, may be the target mechanism for many viral pathogens including coronavirus. Indeed, drug targets in the treatment of COVID19 have been determined by a multi-omics study and DHODH has been identified as one of the three target candidates [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the combination of DPY with inhibitors of de novo pyrimidine biosynthesis has been investigated previously in both in vitro studies and clinical trials to increase the anticancer effects of the latter, the potential of this combination against virus infections has not yet been thoroughly investigated. To this regard, it has been reported very recently the efficacy of a combination of a hDHODH inhibitor, GSK983, with a pyrimidine salvage inhibitor such as the cyclopentenyl uracil (CPU) in suppressing the in vitro replication of dengue virus, even in the presence of physiological concentrations of uridine (Liu et al, 2020). CPU is a uridine analogue able to block the activity of uridine/cytidine kinase 2 (Cysyk et., 1995), a cellular enzyme that phosphorylates uridine to UMP in the pyrimidine ribonucleotide salvage pathway, and therefore acting at a stage downstream from that targeted by DPY (Fitzgerald, 1987).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%